MARRIAGE AGREEMENTS AND ASSET CONFISCATION IN MONEY LAUNDERING: INDONESIAN COURT ANALYSIS - Usanti, Trisadini Prasastinah; Aryatie, Indira Retno; Limantara, Vanessa Widya (jfpublisher, 2025)
This study examines the legal position of marriage agreements that eliminate joint property formation when money laundering crimes occur, focusing on the tension between contractual property separation and criminal asset confiscation. Using normative legal research methods with statutory and case analysis approaches, this study analyzes Indonesian marriage law, anti-money laundering legislation, and judicial decisions, specifically Decision Number 70/Pid.Sus-TPK/2024/PN.Jkt.Pst and its appellate decision Number 1/Pid.Sus-TPK/2025/PT DKI. The findings reveal that while marriage agreements provide legal protection for individual property rights, courts apply the